Sistemas de iluminação e seus efeitos visuais e não visuais: estudo de caso: estabelecimentos assistenciais de saúde para idosos - Carmo, Gilson Werneck do (2017)
Light perceived by the vision system is responsible not only for the perception of images through the cerebral cortex, but also for a series of endocrine processes commanded by the hypothalamus, an organ not related to image formation. The quality of lighting systems proves to be an important environmental factor that can affect the human organism in various ways, and its adequate dimensioning is an environmental management tool. The present work aims at the analysis of the natural and artificial lighting systems of the hospitalization sectors of health care establishments for the elderly and the visual and non - visual effects resulting from their use. The methodology adopted for this study is a multiple case study, analyzing two health care establishments with distinct characteristics located in the Metropolitan Region of Curitiba (MRC). Measurements were made of the natural and artificial lighting systems and the interaction of the two systems of some apartments / wards of the sites surveyed for the diagnosis of the existing situation. The results were compared with values recommended by the Brazilian standards of lighting engineering with regard to visual or image formation effects. For the analysis of non-visual or non-image-forming effects, the spectral variations and circadian stimulus (CS) measurement were evaluated. A computer model of the rooms in the two healthcare units was developed for use in a lighting simulation program, in which the results of the direct measurements were inserted, as a means of verifying the results. Equivalent illuminance curves were prepared for the measured locations, while and lighting conditions were simulated for the rooms not accessible during the study. Simulations were done for different dates of the year in the same sky conditions and time of direct measurements. The result shows that lighting in the patients' dwelling spaces presents important deficiencies that can affect their health. The author proposes the use of the method described herein for evaluating illumination systems of healthcare spaces, and makes design and architectural recommendations regarding lighting, among others. This work is expected to provide information about the real quality of the set of lighting sources used in healthcare units, as well as to propose solutions that provide comfort and wellbeing to elderly users.